Annotation of gene loci and analysis of expression diversity in sheep immunoglobulin - Wu, Mingli; Chen, Fuwen; Tang, Xiaoqin; Li, Jingxuan; Zhao, Haidong; Zhang, Yuelang (Frontiers in Immunology, 2025)
As an important livestock species, sheep exhibit remarkable environmental adaptability. Immunoglobulins, expressed by B cells, are among the most crucial effector molecules in adaptive immunity. However, systematic research on the structure and expression diversity of the sheep immunoglobulins gene loci remains limited. This study annotated the sheep IgH, Igκ, and Igλ loci based on the sheep genome assembly (ARS-UI_Ramb_v3.0). The sheep IgH is located on chromosome 18 and comprises 22 VH, 4 DH, and 6 JH. The Igκ is on chromosome 3, containing 18 Vκ and 4 Jκ. The Igλ is situated on chromosome 17 and consists of 128 Vλ and 3 Jλ. Rearranged IgH, Igκ, and Igλ sequences were obtained from sheep spleen using 5’ RACE PCR. Following PE300 high-throughput sequencing, we analyzed the diversity of V, D, J expression diversity, V(D)J recombination, junctional diversity, and somatic hypermutation in the rearranged sequences. For IgH rearrangement, 4 VH, 4 DH, and 2 JH gene segments were utilized, generating 26 distinct rearrangement types. Igκ rearrangement employed 5 Vκ and 3 Jκ gene segments, resulting in 13 rearrangement types. Igλ rearrangement involved 26 Vλ and 2 Jλ gene segments, producing 28 rearrangement types. Average length of sheep CDR3H is 44 bp (maximum 66 bp), CDR3κ averages 27 bp (maximum 48 bp), and CDR3λ averages 30 bp (maximum 47 bp). N-nucleotide additions contributed more significantly to CDR3 diversity than P-nucleotides in both Igκ and Igλ rearrangements. Simultaneously, 3’ V-deletion and 5’ J-deletion further enriched CDR3 diversity. SHM, especially the hotspot mutation motifs, enriches the diversity caused by the V gene segments. Thus, sheep enrich immunoglobulin diversity through both junctional diversity-driven CDR3 diversification and high-intensity SHM. This study expands our understanding of the sheep immunoglobulin gene loci and their expression diversity, providing theoretical foundation for research on immunoglobulin gene evolution within the Bovidae family.